Stitching of tyrosine and 10H-acridin-9-one: turn-ON fluorescence in the narrow pH range 7.4–8.5 and intracellular labelling of cancer cells12. Issue 4 (19th January 2016) - Singh, Palwinder; Kumar, Arun; Kaur, Sukhmeet; Singh, Amrinder; Gupta, Muskan; Kaur, Gurcharan
Abstract : We tailored 10 H -acridin-9-one and ( S )-tyrosine into 3-(4-hydroxyphenyl)-2-[(9-oxo-9, 10-dihydroacridine-4-carbonyl) amino]propionic acid (2 ). Abstract : We tailored 10 H -acridin-9-one and ( S )-tyrosine into 3-(4-hydroxyphenyl)-2-[(9-oxo-9, 10-dihydroacridine-4-carbonyl) amino]propionic acid (2 ).2 underwent pH dependent protonation/deprotonation and the effect was harnessed in terms of change in the fluorescence. The characteristic fluorescence change in the molecule in the pH 7.5 ± 1 range and its cell permeability allowed us to label cancer cells.